تبني البنوك التجارية التقليدية للمعاملات المصرفية الإسلامية - زرفاط, خليدة; سوالمي, رحاب نور الهدى (جامعة ابن خلدون-تيارت, 2023)
تمثل البنوك التجارية الجزائرية المعبر الرئيسي للوساطة المالية والمصرفية في الاقتصاد الوطني، إذ تساهم بشكل كبير في أغلب المعاملات الاقتصادية داخل وخارج الوطن، وبالتالي فهي تساهم بعدة أدوار مهمة في التنمية الاقتصادية واستدامتها عبر الأجيال، قام ت الحكومة بإنشاء فروع ونواف ذ إسلامية للمعاملات المالية الإسلامية على مستوى هذه البنوك وطرح منتجات مصرفية إسلامية قرر ساعد على جذب المتعاملين بالسوق الموازية لضخ أموالهم بالبنوك الوطنية واستخدامها بصيغ تطبق احكام الشريعة الإسلامية، تعمل الصيرفة الإسلامية على نبذ الربا وتعزيز التكافل الاجتماعي والعدالة. إن استخدام مثل هذه الخدمات يهدف إلى تحقيق المشاركة في الأرباح والخسائر بين البنوك والزبائن. وفي دراستنا تبين لنا مدى تبني البنوك التقليدية الجزائرية للمعاملات المالية الإسلامية من خلال فتح نوافذ إسلامية تعمل وفق الشريعة الإسلامية لتحقيق رضا وإستقطاب الزبائن Algerian commercial banks represent the main catalyst for financial and banking intermediation in the national economy. They to contribute significantly the majority of economic transactions within and outside the country. Consequently, they play several crucial roles in economic development and its sustainability across generations. The government has established branches and windows for Islamic financial transactions in these banks and introduced Islamic banking products. This decision has helped attract participants in the parallel market to channel their funds into national banks and utilize them in accordance with Islamic law principles. Islamic banking aims to eliminate usury (riba) and promote social solidarity and justice. The use of such services aims to achieve profit and loss sharing between banks and customers. Our study has revealed the extent to which Algerian traditional banks have embraced Islamic financial transactions by opening Islamic windows that operate in accordance with Islamic law, aiming to achieve customer satisfaction and attract clients
Keywords: Commercial banks; Customer satisfaction; Financial transactions; Islamic Banking; Islamic windows

تحديات فرض الضرائب على معاملات التجارة الإلكترونية في الجزائر - مبخوت, رفيق; غول, حسين (Ibn Khaldun University of Tiaret, 2023)
لقد تطرّقنا في موضوع دراستنا على تحدّيات فرض الضّرائب على معاملات التّجارة الإلكترونية باعتبار موضوع التّجارة الإلكترونية من المواضيع الهامّة التي تلقى اهتماما كبيرا من قبل الكثير من الباحثين لما لها من انعكاسات على اقتصاديات دول العالم المتقدّمة والنّامية، حيث تعدّ إحدى النّظم الحديثة في إتمام وتنفيذ المعاملات التّجارية عبر شبكات الأنترنت. ولقد أسفرت دراستنا الميدانية في المركز الجواري للضّرائب دائرة السّوقر التي واجهت عدّة صعوبات لإخضاع المعاملات الإلكترونية بسب غياب قوانين والتّشريعات المتعلّقة بتنظيم الضّريبة الإلكترونية وغياب رقمنة القطاع وصعوبات تقنية تطبيق هذا النّوع من الضّرائب. هذا ما أوجب على الجزائر بذل مجهوداتها من أجل دعم وإرساء البنية التحتية للاتّصالات ومسايرة التّقدّم التّكنولوجي في العالم وتسليط الضّوء على القوانين والتّشريعات الجبائية الخاصّة بهذه التّجارة وسَنّها والعمل بها على أرض الواقع. In the subject of our study, we have addressed the challenges of imposing taxes on electronic commerce transactions, considering the issue of electronic commerce as one of the important topics that receive great attention by many researchers because of its implications for the economies of the developed and developing countries of the world, as it is one of the modern systems in the completion and implementation of commercial transactions. Via internet networks. Our field study resulted in the neighborhood tax center, in Sougueur Department, which faced several difficulties in subjecting electronic transactions due to the absence of laws and legislation related to the organization of electronic taxation, the absence of digitization of the sector, and the technical difficulties of applying this type of taxation. This is what required Algeria to exert its efforts to support and establish the telecommunications infrastructure, keep pace with the technological progress in the world, shed light on the laws and fiscal legislation related to this trade, enact them and implement them on the ground.
Keywords: Algeria; Algérie; Commerce électronique; Fiscalité; Internet; Taxe électronique; الأنترنت; التجارة الإلكترونية; الضريبة الإلكترونية; النظام الضريبي

آليات تقييم الصيرفة الاسلامية في البنوك التجارية وتحدياتها -دراسة حالة البنك الوطني الجزائري - ساعد, بن; الحميد, عبد (Ibn Khaldun University of Tiaret, 2022)
يعتبر النظام المصرفي من بين الأسس التي يعتمد عليها النشاط الاقتصادي لأي مجتمع و ذلك بالنظر لأهمية الدور الذي يلعبه في المساهمة في إمداد النشاط الاقتصادي بالأموال، اللازمة من اجل تنميته و تطوي ره ، وقد اجمع الباحثون الاقتصاديون على أن من بين أسباب الأزمات المالية ترجع إلى الأسلوب الربوي المتبع من طرف البنوك التقليدية، خصوصا بعد أن ضربت الأزمة المالية العالمية عصب الاقتصاد الرأسمالي سنة 2008 وهزت اقتصاديات الدول وأضعفت البنوك التجارية خلافا عن البنوك الإسلامية والبنوك التجارية ذات الشبابيك الإسلامية ، ومن هذا المنطلق ازدادت الحاجة إلى وجود بنوك تعمل وفقا للشريعة الإسلامية والتي تقوم على أساس إلغاء الفائدة وعدم التعامل بالربا في تعاملاتها، ومنه فقد أصبحت هذه البنوك لاعبا مؤثرا وبارزا في اقتصاديات الدول الإسلامية و العالمية و التي من بينها الجزائر التي اتجهت هي الأخرى للدخول إلى عالم الصیرفة الإسلامية باعتمادها لافتتاح نوافذ إسلامية على مستوى البنوك العمومية. ومن خلال دراستنا توصلنا الى أن البنوك العمومية الجزائرية تحاول خوض تجربة فتح شبابيك إسلامية وقد خلصنا بأن اعتماد هذه البنوك على آلية التعامل بشبابيك تعمل وفق قواعد الشريعة الإسلامية في معاملاتها المالية من شأنه أن يحقق استقطاب ورضا الزبائن. The banking system is considered one of the foundations on which the economic activity of any society is based, given the importance of the role, it plays in helping to supply economic activity with the funds necessary for its operation. Economic researchers have agreed that among the causes of financial crises are due to the usurious method adopted by banks, especially after the global financial crisis hit the backbone of the capitalist economy in 2008, shook the economies of the countries, and weakened commercial banks unlike Islamic banks and commercial banks with Islamic windows From this point of view, the need has grown for the existence of bank operating in accordance with Islamic law, which is based on the abolition of interests in their financial transactions, these banks have become an influential and leading actor in the economies of Islamic countries including Algeria, which has also tended to enter the Islamic banking world by adopting it to open Islamic windows at the level of public banks. Through our study, we concluded that Algerian public banks are trying to live with the opening of Islamic counters, and we concluded that the dependence of these banks on the processing mechanism of counters that operate according to the rules of Islamic Sharia law in their financial transactions, would attract and satisfy customers.
Keywords: Banques commerciales; Banques islamiques; Fenêtres islamiques; Satisfaction client; البنوك الإسلامية; البنوك التجارية; النوافذ الإسلامية; رضا الزبائن

Banks responsibility in the collection of the commercial paper contract - Al-Shawabkeh, Wa’ed (Al-Balqa Journal for Research and Studies, 2022)
The importance of studying this contract is to establish the legal nature of the bank’s responsibility when it fails to collect the value of the commercial paper, and to know the role and direction of the judiciary in that respect. The study relied on the element of analysis and education in a brief scientific way. The purpose of the study is to examine the legal basis for the Bank’s responsibility in the collection contract and the general provisions for this responsibility resulting for it, and to cover that responsibility in all its aspects. The study relies on the analytical method in order to achieve the purpose and objectives of the research, where the legal texts will be analyzed and practical results will be reached. In this research legal texts will be analyzed to reach scientific results, the study also reached results, including that there was no regulation from the Jordanian legislator for the collection, in addition to the overlapping of the agency and deposit contracts in the collection contract and that the bank’s responsibility towards its client is a contractual responsibility due to the nature of the relationship between them. The research recommends that the Jordanian Trade law should include special texts dealing with the collection contract, and that the judiciary be more present while evaluating the nature of the relationship and the basis of responsibility between the bank and its client, and it should be clearly stated that the bank may require the disqualification of itself from the liability resulting from collection contract.

The Ability of Short-term Accounting Accruals to Predict Cash Flows of Algerian Companies - Bilal, Kimouche (An-Najah University Journal for Research - B (Humanities), 2020)
هدفت الدراسة إلى استكشاف مدى قدرة المستحقات المحاسبية قصيرة األجل على التنبؤ بالتدفقات النقدية، حيث شملت 14 شركة جزائرية بين 2003 و،2015 ليبلغ عدد المشاهدات الكلية خالل الفترة 117 مشاهدة. وقد تم قياس التدفقات النقدية بصافي التدفقات النقدية التشغيلية، وتم التعبير عن المستحقات المحاسبية قصيرة األجل بـ: التغير في حسابات الزبائن والمدينين، التغير في حسابات الموردين والدائنين، والتغير في المخزونات. وقد أثبتت النتائج ضعف قدرة المستحقات المحاسبية قصيرة األجل على التنبؤ بالتدفقات النقدية للفترة المقبلة، حيث كانت عالقة هذه األخيرة ببنود المستحقات المحاسبية قصيرة األجل غير معنوية، باستثناء عالقتها بالتغير في حسابات الموردين والدائنين This study aims to explore the ability of short-term accounting accruals to predict cash flows. It included 117 observations during 2003 to 2015, which concern 14 Algerian companies. Cash flows have been measured by operating cash flow (OCF). However, short-term accounting accruals have been expressed by change of accounts receivable and debtors, change of accounts payable and creditors, and change of inventories. The results indicated a failure of current short-term accounting accruals to predict cash flows of next period. Except for change of accounts receivable and debtors, the correlations of future operating cash flows with other Short-term accounting accrual items are not significant.
Keywords: Cash flows; Change of accounts payable and creditors; Change of accounts receivable and debtors; Change of inventories; Long-term accounting accruals; Short-term accounting accruals

دور البنوك التجارية في مكافحة عمليات غسيل الأموال - بومدين, نبية (Ibn Khaldun University of Tiaret, 2020)
تعتبر البنوك التجارية من أهم المحطات المالية التي تقوم بعمليات قبول الودائع ودفعها عند الإستحقاق كما تساهم في عملية خلق النقود بكميات كبيرة هذا ما جعلها الأكثر عرضة لجريمة غسيل الأموال والغاية من هذا هو معرفة كيف تكافح هذه البنوك لجريمة خطيرة مثل هذه والتي سادت كل العالم هذا ما أدى إلى دراستنا لهذا الموضوع الذي إعتمدنا فيه على المنهج الوصفي التحليلي و بالتالي عند دراستنا له توصلنا إلى مجموعة من النتائج تتجلى في معرفة الظاهرة بأنها ظاهرة خطيرة سريعة الإنتشار ،عرضة البنوك بهذه الظاهرة كونها تقوم بعدة عمليات ،وجوب على الدولة أن تكافح هذه الجريمة وذلك بوضع قوانين تشريعية تعاقب كل من قام بإرتكاب هذه الظاهرة الخطيرة. Commercial banks are considered one of the most important financial stations that carry out the processes of accepting and paying deposits at maturity and also contribute to the process of creating money in large quantities. This led to our study of this subject, in which we relied on the descriptive and analytical approach, and therefore upon our study of it, we reached a set of results that are evident in the knowledge of the phenomenon that it is a dangerous and rapidly spreading phenomenon. The banks are exposed to this phenomenon as they carry out several operations. Legislative laws punishing anyone who committed this dangerous phenomenon.
Keywords: Banques commerciales; Blanchiment d'argent; Système bancaire; البنوك التجارية; الجهاز المصرف; جريمة غسيل الاموال